Strategi Pengembangan Kemampuan Numerik Anak Usia Dini - Masamah, Ulfa (THUFULA, 2017)
Child at the age of zero to five years is seen as a golden age (golden age) to learn because in this age range their growth and development takes place quickly and rapidly. One is the Son has the informal mathematical knowledge is incredible. On this basis, educators need to provide the right stimuli that optimal child growth and development. This research is literature. The research results indicate that the child has an informal mathematical knowledge gained extraordinary and studied in the context of everyday life. It is important for children to understand the concept that teaches mathematics first is through the use of mathematical intuition contextual and then to mathematical symbols. Symbols are then abstracted by the children in his brain, this is called a visual representation (visual imagery). Mental imagery (mental imagery) as an object mentally for reflective thinking processes that will help and guide individuals to solve problems as well as helping individuals to reorganize (construct) a wide range of knowledge and reconstruct the concept of the problem. Therefore, context familiarity, ease of substance, the attractiveness of the object, and fun activities become a keyword in teaching mathematics in early childhood.